1988
DOI: 10.1080/07315724.1988.10720215
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium therapy in premature neonates with apnea neonatorum.

Abstract: Apnea, bradycardia, and neuromuscular hyperirritability have been associated with magnesium (Mg) deficiency in young human infants and weanling animals. This is a retrospective review of a clinical experience of Mg therapy among 200 premature neonates who showed physical and clinical chemical changes compatible with Mg deficiency. The 200 infants all had idiopathic apnea neonatorum, and 93% also had the respiratory distress syndrome (RDS). This review was conducted to learn whether Mg therapy was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Wirth et al (1990) fed 19 mg/100 kcal for 6 days to preterm-LBW infants without reports of adverse effects. Caddell (1988; administered 24 mg of magnesium during a 24-hour period, orally as the chloride, usually for 2 weeks, to 200 premature infants with apnea neonatorum. She reported that none of the infants showed signs of magnesium toxicity.…”
Section: Toxicitymentioning
confidence: 99%
“…Wirth et al (1990) fed 19 mg/100 kcal for 6 days to preterm-LBW infants without reports of adverse effects. Caddell (1988; administered 24 mg of magnesium during a 24-hour period, orally as the chloride, usually for 2 weeks, to 200 premature infants with apnea neonatorum. She reported that none of the infants showed signs of magnesium toxicity.…”
Section: Toxicitymentioning
confidence: 99%
“…Miller et al [120] suggest that abnormal blood platelet activation may be a significant mortality risk factor in severe gestational and infantile Mg deficit and draw a parallel between the pathologic findings in Mg deficient lambs with those in the sudden infant death syndrome (SIDS). Caddell proposes that neonatal and postneonatal apnea and respiratory distress syndrome (RDS) are pre monitory findings in infants who are later victims of SIDS, and advises Mg treatment in doses low enough not to constitute a risk (0.4-1 mEq/kg/d for about 2 weeks) in RDS infants with immature kidneys [121][122][123]. Infants with RDS are most commonly born to mothers subject to hypomagnesemia [59,124].…”
Section: Relationships Of Perinatal Mg Deficiency To Infantile Reactimentioning
confidence: 99%
“…1) and lambs in which intravascular clumping of platelets was induced by collagen injected intravenously [23] were markedly similar to lungs of an 11-week-old human infant diag nosed as a victim of SIDS [5]. Clinical experience with idiopathic apnea neonatorum [24] revealed no record of hospital readmission for recurrent apnea or death in 61 infants receiving Mg therapy (0.4 mEq intramuscularly as the sulfate or 1.0 mEq orally as the chloride/kg body weight/day) a minimum of 5 days. In contrast, among 134 infants receiving Mg less than 2 days (mean = 0.5 days), 32 developed recurrent apnea, of which four died of SIDS.…”
Section: Spontaneous Death Of Lambs During Clinical Hypomagnesemiamentioning
confidence: 99%